2018
DOI: 10.3389/fchem.2018.00535
|View full text |Cite
|
Sign up to set email alerts
|

Water-Tolerant Trifloaluminate Ionic Liquids: New and Unique Lewis Acidic Catalysts for the Synthesis of Chromane

Abstract: The first example of triflometallate ionic liquids, named in analogy to chlorometallate ionic liquids, is reported. Trifloaluminate ionic liquids, synthesized from 1-alkyl-3-methylimidazolium triflates and aluminum triflate, were characterized by multinuclear NMR spectroscopy and FT-IR spectroscopy, revealing the existence of oligonuclear, multiply-charged trifloaluminate anions, with multiple bridging triflate modes. Acceptor numbers were determined to quantify their Lewis acidity, rendering trifloaluminate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…Sun et al demonstrated that ethanolamine acetate was effective to produce cellulosic ethanol from switch grass in one-pot process (Sun et al, 2017). In addition to the consideration of cationic species, anions are also significant in the process of designing PILs in that the anions of PILs, as a kind of deprotonated acids, play crucial roles in many fields, like catalysis, gas absorption as well as biomass pretreatment and so on (Latos et al, 2018; Ren et al, 2018). Therefore, the combination of acidic anions and basic cations with various functional groups of PILs foreshadows a lot of meaningful and useful properties, which can widen potential applications of this type of PILs.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al demonstrated that ethanolamine acetate was effective to produce cellulosic ethanol from switch grass in one-pot process (Sun et al, 2017). In addition to the consideration of cationic species, anions are also significant in the process of designing PILs in that the anions of PILs, as a kind of deprotonated acids, play crucial roles in many fields, like catalysis, gas absorption as well as biomass pretreatment and so on (Latos et al, 2018; Ren et al, 2018). Therefore, the combination of acidic anions and basic cations with various functional groups of PILs foreshadows a lot of meaningful and useful properties, which can widen potential applications of this type of PILs.…”
Section: Introductionmentioning
confidence: 99%
“…Plausible anionic species present in trifloaluminate ionic liquids, close to the maximum loading of Al(OTf)3: [Al2(OTf)10] 4and [Al3(OTf)14] 5-. 14 In our previous work, trifloaluminate ionic liquids have been used as efficient acid catalysts in a solventfree, one-pot syntheses of chromane. 14 It was found that immobilisation of trifloaluminate ionic liquids onto multi-wall carbon nanotubes (MWCNTs) 17 to form a supported ionic liquid phase (SILP) offered numerous advantages in terms of product separation, catalyst stability, and recycling.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have reported the first example of ionic liquids (ILs), where the traditional chlorido ligands on aluminium are replaced with trifluoromethanesulfonate (triflate, OTf) ligands. 14 oligonuclear anionic complexes, with a variety of triflate bridging modes (Scheme 2). 14 As a consequence, they are more viscous and higher melting than the chloroaluminate analogues, but have significantly improved stability against the atmospheric moisture.…”
Section: Introductionmentioning
confidence: 99%
“…introduced new MWCNTs supported trifloaluminate IL that acted as a catalyst in the [3+3] cycloaddition reaction to prepare chromanes. The heterogeneous catalyst was tailored by immobilizing the mixture of imidazolium IL and lewis acidic aluminum triflate (Al(OTf) 3 ) onto MWCNTs (Table , Entry 4) …”
Section: Synthesis and Applications Of Sils Having Different Buildingmentioning
confidence: 99%